Kendali Genetik Karakter Morfologi dan Agronomi pada Tiga Populasi Sorgum (Sorghum bicolor (L.) Moench) - ,, Trikoesoemaningtyas; Wirnas, Desta; Saragih, Ery Leonardo; Rini, Erin Puspita; Sari, Mayang; Marwiyah, Siti; Sopandie, dan Didy (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
ABSTRACT Sorghum is one of the potential foods with a higher protein content than rice. Sorghum seeds can be milled and cooked as sorghum rice. This study was aimed to obtain information on the inheritance of morphological and agronomic characters from the population derived from crosses of wide genetic background. The study consisted of the formation of F1 population and evaluation of morphological and agronomic characters in the segregated population (F2) of the three selected F1 genotypes. The location of the research was at IPB Experimental Field, Leuwikopo. The performance of the F1 genotypes were between the two parents, except for the yield components of PI-150-20-A x Numbu and PI-150-20-A x Kawali were higher than the parental lines. The performance of the F2 generation population was also between the parental lines, but with a wider distribution. The sorghum seed color is controlled not only by additive and dominant gene action, but also by epistatic gene action. The character of seed weight per panicle is controlled by epistatic gene action. In the F2 population of the crosses of PI-150-20-A x Numbu and PI-150-20-A x Kawali and PI-10-90-A x Numbu, the seed weight character is inherited with moderate heritability value. Based on genes action dan heritability, bulk or single seed descent method are suitable for yield improvement of the populations.Keywords: gene action, heritability, seed color, segregation, sorghum